A Methodology for Mapping the Patient Journey for Noncommunicable Diseases in Low- and Middle-Income Countries - Bharatan T; Devi R; Huang PH; Javed A; Jeffers B; Lansberg P; Sidhu K; Subramaniam K (Dove Medical Press, 2021)
Tanaya Bharatan,1 Ratna Devi,2,3 Pai-Hui Huang,4 Afzal Javed,5 Barrett Jeffers,6 Peter Lansberg,7 Kaveri Sidhu,1 Kannan Subramaniam8 1Research Development & Medical, Upjohn Division, Pfizer Ltd, Mumbai, India; 2Executive Office, Daksham A Health and Education, Gurgaon, India; 3International Alliance of Patient Organizations, London, UK; 4Medical Affairs, Viatris, Taipei, Taiwan; 5Warwick Medical School, University of Warwick, Warwick, UK; 6Medical Affairs, Viatris Inc, New York, NY, USA; 7Department of Pediatrics, University Medical Center, Groningen, the Netherlands; 8Medical Affairs, Viatris | Mylan New Zealand Ltd, Auckland, New ZealandCorrespondence: Kannan SubramaniamViatris | Mylan New Zealand Ltd, PO Box 11183, Ellerslie, Auckland 1542, New ZealandTel +64 21 592 064Fax +61 2 8080 8181Email kannan.subramaniam@viatris.comAbstract: Noncommunicable diseases (NCDs) are responsible for 71% of all worldwide mortality each year, and have an exceptionally large impact in low- and middle-income countries (LMICs). However, there is often a lack of local data from these countries to inform practice and policy improvements. Generating locally contextualized evidence base for NCDs that can help identify gaps, aid decision-making and improve patient care in LMICs needs an innovative approach. The approach used in Mapping the Patient Journey Towards Actionable Beyond the Pill Solutions (MAPS) is designed to quantitatively map different stages of the patient journey in four critical NCDs, ie, hypertension, dyslipidemia, depression, and pain (chronic and neuropathic) across selected LMICs in Africa, the Middle East, South East Asia, and Latin America. The key touchpoints along the patient journey include awareness, screening, diagnosis, treatment, adherence, and control or remission. MAPS employs an evidence mapping methodology that follows a three-step semi-systematic review: 1) systematic peer-reviewed database search; 2) unstructured searches of local or real-world data; and 3) expert opinion. Evidence generation and visualization is based on locally validated and deduplicated data published over the last 10 years. This approach will be the first to provide quantitative mapping of the different stages of the patient journey for selected NCDs in LMICs. By focusing on local, patient-centric data, the goal of the MAPS initiative is to address and prioritize local research and knowledge gaps, then contribute to evidence-based, high-quality, and affordable advances in the management of NCDs in LMICs. This will ultimately improve patient outcomes and contribute towards the achievement of global NCD targets.Keywords: noncommunicable diseases, low- and middle-income countries, decision-making, patient journey, evidence mapping